Optimized signal peptides for the development of high expressing CHO cell lines - Kober, Lars; Zehe, Christoph; Bode, Juergen (Biotechnology and bioengineering, 2013)
Recombinant biotherapeutic proteins such as monoclonal antibodies are mostly produced in Chinese hamster ovary (CHO) cells and pharmaceutical companies are interested in an appropriate platform technology for the development of large‐scale production processes. A major aim of our study was therefore to improve the secretion efficiency of a recombinant biotherapeutic antibody by optimizing signal peptides. Reporter molecules such as gaussia and vargula luciferase or secreted alkaline phosphatase are frequently used to this end. In striking contrast, we used a biotherapeutic antibody that was fused to 16 different signal peptides during our study. In this way, the secretion efficiency of the recombinant antibody has been analyzed by transient expression experiments in CHO cell lines. Compared to the control signal peptide, it was not possible to achieve higher efficiencies with signal peptides derived from a variety of species or even natural immunoglobulin G signal peptides. The best results were obtained with natural signal peptides derived from human albumin and human azurocidin. These results were confirmed by fed‐batch experiments with stably transfected cell pools, in which cell‐specific productivities up to 90 pg cell−1 day−1 and product concentrations up to 4 g L−1 could be determined using the albumin signal peptide. Finally, the applicability of the identified signal peptides for both different antibodies and non‐antibody products was demonstrated by transient expression experiments. In conclusion, it was found that signal peptides derived from human albumin and human azurocidin are most appropriate to generate cell lines with clearly improved production rates suitable for commercial purposes in a product‐independent manner. Biotechnol. Bioeng. 2013; 110: 1164–1173. © 2012 Wiley Periodicals, Inc. Highly productive cell lines are required for the production of biopharmaceutical products. To this end a variety of signal peptides was used to express different antibodies and non‐antibody products in transiently and stably transfected Chinese hamster ovary (CHO) cells. Thereby it could be demonstrated that signal peptide B, but also signal peptide E can be used to generate cell lines with cell specific productivities (QP) up to 60 or 90 pg antibody/cell/day (pcd mean values are represented by red bars).